Testing Milbrath’s 1965 Framework of Political Participation: Institutions and Social Capital - Ruedin, Didier (My University, 2007)
Despite its age, Milbrath’s 1965 framework of political participation is still widely cited. A computer simulation is used to empirically test the framework for the first time. The parameter estimates from the simulation provide valid results, suggesting that the framework may be viable. The simulation is then used to explore the nature of political participation. It is found that both political institutions and social capital are significant contributors to political participation. The role of social capital is revised: rather than the time spent in a community, personal contacts appear to be more important for political participation.